Design And Development Of Basic Teaching Modules For Open Source JaamSim Discrete Event Simulation Software - Ibrahim, Nurul Hakimi (Universiti Sains Malaysia, 2018)
This final year project report presents the design of a teaching module of JaamSim Discrete Event Simulation Software. The objective of this project was to design and develop teaching modules for JaamSim discrete event simulation software. The problem was because there are limited resources of teaching module available and the accessibility of using WITNESS. The next objective of this project, was to build a simulation model using JaamSim simulation software. The teaching module design will help new user to use the module to build a simulation model using JaamSim simulation software. The design description of this teaching module was to designed step by step to ease the new user. The content of the teaching module is designed based on an industrial case study in a coffee factory. Lastly, the evaluation of the simulation is analyzed based on the functions of the cooling and grinding simulation model.